Genetic diversity and population structure of an endemic bee Wallacetrigona incisa in South Sulawesi, Indonesia - ANDI GITA MAULIDYAH INDRASWARI SUHRI; PHIKA AINNADYA HASAN; IRNAYANTI BAHAR; HEARTY SALATNAYA; FATHIMAH NURFITHRI HASHIFAH; MUFTI HATUR RAHMAH; SUCI WULANDHANI; HUSNI MUBAROK; WIWIK WIJI ASTUTI (Society for Indonesian Biodiversity, 2025)
Abstract. Suhri AGMI, Hasan PA, Bahar I, Salatnaya H, Hashifah FN, Rahmah MH, Wulandhani S, Mubarok H, Astuti WW. 2025. Genetic diversity and population structure of an endemic bee Wallacetrigona incisa in South Sulawesi, Indonesia. Biodiversitas 26: 861-868. Stingless bees are vital pollinators for biodiversity, yet their genetic diversity and population dynamics in isolated regions like Sulawesi, Indonesia, remain poorly understood. A stingless bee species in the highland regions of Sulawesi, Wallacetrigona incisa, was investigated for its genetic variability, population dynamics, and environmental influences. This study aimed to clarify the genetic basis of the different populations in the highlands and lowlands. Inbreeding rates, population structure, and genetic exchange were assessed using molecular markers. The results showed low levels of inbreeding across populations with minor geographic differences, indicating that gene flow is still occurring between populations. Population structure analysis identified two distinct genetic groups, a highland group and a lowland group, suggesting strong genetic divergence, possibly due to geographical isolation. The association with over-winter survival in this study was the broad climate variables floral abundance and temperature. The results indicate that floral richness, particularly in highland regions, predicts genetic diversity better than temperature. These findings suggest that environmental variables, especially floral diversity, are particularly important for shaping W. incisa population genetics. Our study contributes new knowledge to W. incisa conservation and management by revealing that floral richness, particularly in highland regions, strongly influences genetic diversity and population robustness, underscoring the necessity of preserving diverse floral habitats. Additionally, this research contributes to our knowledge of the impacts of geographic and environmental factors on the genetic diversity of stingless bees and provides a valuable basis for future conservation efforts on a large scale in Sulawesi and other similar ecological areas.